Cyclic AMP in Mycobacteria: Characterization and Functional Role of the Rv1647 Ortholog in Mycobacterium smegmatis - Dass, Bob Kennedy M. (American Society for Microbiology (ASM), 2008)
Mycobacterial genomes are endowed with many eukaryote-like nucleotide cyclase genes encoding proteins that can synthesize 3′,5′-cyclic AMP (cAMP). However, the roles of cAMP and the need for such redundancy in terms of adenylyl cyclase genes remain unknown. We measured cAMP levels in Mycobacterium smegmatis during growth and under various stress conditions and report the first biochemical and functional characterization of the MSMEG_3780 adenylyl cyclase, whose orthologs in Mycobacterium tuberculosis (Rv1647) and Mycobacterium leprae (ML1399) have been recently characterized in vitro. MSMEG_3780 was important for producing cAMP levels in the logarithmic phase of growth, since the ΔMSMEG_3780 strain showed lower intracellular cAMP levels at this stage of growth. cAMP levels decreased in wild-type M. smegmatis under conditions of acid stress but not in the ΔMSMEG_3780 strain. This was correlated with a reduction in MSMEG_3780 promoter activity, indicating that the effect of the reduction in cAMP levels on acid stress was caused by a decrease in the transcription of MSMEG_3780. Complementation of the ΔMSMEG_3780 strain with the genomic integration of MSMEG_3780 or the Rv1647 gene could restore cAMP levels during logarithmic growth. The Rv1647 promoter was also acid sensitive, emphasizing the biochemical and functional similarities in these two adenylyl cyclases. This study therefore represents the first detailed biochemical and functional analysis of an adenylyl cyclase that is important for maintaining cAMP levels in mycobacteria and underscores the subtle roles that these genes may play in the physiology of the organism.